A Hermeneutical Study On The Symbolic Meaning Of The Number 144.000 In Revelation 7:1-17 - Camerling, Yosua Feliciano; Panggarra, Robi; Kanna, Armin Sukri; Laukapitang, Yunus Daniel Anus (Jurnal Jaffray, 2021)
This study aims to analyze and reveal the symbolic meaning of “the number those who were sealed: 144,000 from all the tribes of Israel” in Revelation 7:1-17 and implications for the mission. The research method used is qualitative research carried out with the principles and hermeneutic methods of the Bible. The Bible’s hermeneutic method is divided into two characteristics, namely general hermeneutics and specific ones. For the general hermeneutic interpretation method, the author uses three existing analyses structural analysis, grammatical analysis and theological analysis. Then for the particular hermeneutic interpretation method, the author uses the interpretation of number symbols. The results of this study reveal that the symbolic meaning of “the number those who were sealed: 144,000 from all the tribes of Israel” in Revelation 7:1-17 are symbolic numbers of the number redeemed by the Lamb who made it through the tribulation period by remaining faithful to the end of being followers of Christ. As for the theological implications of the text of Revelation 7:1-17 for the mission, namely, God Protects His People (7:1-3), God is Consistent with His Promise of Salvation (7:4-8), and God Grants Universal Salvation (7:9-17). As for the practical implications of the text of Revelation 7: 1-17 for the mission, namely Believers are sealed as servants of God (7:1-8), Believers glorify God (7:9-12), and Believers receive sanctification and God's providence (7:13- 17).